2012
DOI: 10.1007/s11434-012-4974-9
|View full text |Cite
|
Sign up to set email alerts
|

Energetic electrons associated with magnetic reconnection in the sheath of interplanetary coronal mass ejection

Abstract: Magnetic reconnection is an important universal plasma dissipation process that converts magnetic energy into plasma thermal and kinetic energy, and simultaneously changes the magnetic field topology. In this paper, we report the first observation of energetic electrons associated with asymmetric reconnection in the sheath of an interplanetary coronal mass ejection. The magnetic field shear angle was about 151°, implying guide-field reconnection. The width of the exhaust was about 8×10 4 km. The reconnection r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Energetic electrons with energies of hundreds of keV have been observed in the reconnection diffusion region [ Øieroset et al , 2002; He et al , 2008; Retinò et al , 2008], outflow region [ Imada et al , 2007; Huang et al , 2012], and within magnetic islands [ Chen et al , 2008; Retinò et al , 2008; Wang et al , 2010]. Recently, Imada et al [2011] have studied favorable conditions for energetic electron acceleration using 10 reconnection events observed by Geotail, and found that the electrons are efficiently accelerated in a thin CS during magnetic reconnection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Energetic electrons with energies of hundreds of keV have been observed in the reconnection diffusion region [ Øieroset et al , 2002; He et al , 2008; Retinò et al , 2008], outflow region [ Imada et al , 2007; Huang et al , 2012], and within magnetic islands [ Chen et al , 2008; Retinò et al , 2008; Wang et al , 2010]. Recently, Imada et al [2011] have studied favorable conditions for energetic electron acceleration using 10 reconnection events observed by Geotail, and found that the electrons are efficiently accelerated in a thin CS during magnetic reconnection.…”
Section: Discussionmentioning
confidence: 99%
“…Energetic electrons are important consequences of magnetic reconnection [e.g., Hoshino et al , 2001; Drake et al , 2006a; Pritchett , 2006], and have been observed associated with reconnection [e.g., Øieroset etal. , 2002; Imada et al , 2007; Retinò et al , 2008; Huang et al , 2012]. Magnetic islands are closely related to electron acceleration during reconnection.…”
Section: Introductionmentioning
confidence: 99%
“…However, the net energy increment of this trapped cold ion is only 𝐴𝐴 ∼ 0.08 𝑚𝑚𝑖𝑖𝑣𝑣 2 𝐴𝐴 at 𝐴𝐴 𝐴𝐴= 47.5 . Previous studies suggest that electrons can be energized significantly in secondary islands (e.g., Huang et al, 2012;Zhong et al, 2020). Here we do not see obvious electron energization within this secondary island, similar to cold ions.…”
Section: Energization By Reconnectionmentioning
confidence: 99%
“…2003; Gosling et al 2007;Wang et al 2010;Chian & Muñoz 2011) and numerical experiments (e.g., Schmidt & Cargill 2003;Wang et al 2010) that magnetic reconnection can occur at the interface between the leading edge of interplanetary coronal mass ejections (ICMEs) and background solar wind magnetic field (see also Démoulin 2008). Such episodes of magnetic reconnection could supply beams of suprathermal and/or nonthermal energetic electrons to the sheath region (Wang et al 2010;Huang et al 2012), thus possibly creating the necessary conditions for generation of the Langmuir turbulence and radio emission there. However, we realize (and emphasize) that this important issue requires further studies.…”
Section: Scenariomentioning
confidence: 99%